Infectious complications after out-of-hospital cardiac arrest—A comparison between two target temperatures. (April 2017) - Dankiewicz, Josef; Nielsen, Niklas; Linder, Adam; Kuiper, Michael; Wise, Matthew P.; Cronberg, Tobias; Erlinge, David; Gasche, Yvan; Harmon, Matthew B.; Hassager, Christian; Horn, Janneke; Kjaergaard, Jesper; et al.
Abstract: Background: It has been suggested that target temperature management (TTM) increases the probability of infectious complications after cardiac arrest. We aimed to compare the incidence of pneumonia, severe sepsis and septic shock after out-of-hospital cardiac arrest (OHCA) in patients with two target temperatures and to describe changes in biomarkers and possible mortality associated with these infectious complications. Methods: Post-hoc analysis of the TTM-trial which randomized patients resuscitated from OHCA to a target temperature of 33 °C or 36 °C. Prospective data on infectious complications were recorded daily during the ICU-stay. Pneumonia, severe sepsis and septic shock were considered infectious complications. Procalcitonin (PCT) and C-reactive-protein (CRP) levels were measured at 24 h, 48 h and 72 h after cardiac arrest. Results: There were 939 patients in the modified intention-to-treat population. Five-hundred patients (53%) developed pneumonia, severe sepsis or septic shock which was associated with mortality in multivariate analysis (Hazard ratio [HR] 1.39; 95%CI 1.13–1.70; p = 0.001). There was no statistically significant difference in the incidence of infectious complications between temperature groups (sub-distribution hazard ratio [SHR] 0.88; 95%CI 0.75–1.03; p = 0.12). PCT and CRP were significantly higher for patients with infections at all times (p < 0.001), but there was considerable overlap. Conclusions: Patients who develop pneumonia, severe sepsis or septic shock after OHCA might have an increased mortality. A target temperature of 33 °C after OHCA was not associated with an increased risk of infectious complications compared to a target temperature of 36 °C. PCT and CRP are of limited value for diagnosing infectious complications after cardiac arrest.